Antara Harapan dan Realita: Integrasi Teknologi Informasi dalam Pelayanan Administrasi Haji untuk Meningkatkan Transparansi dan Akuntabilitas Publik - Anas AN, Nashrul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Currently, almost all government agencies are maximizing the use of information technology (IT) in their services, including the Ministry of Religious Affairs in its services to Indonesian hajj pilgrims. This is a new hope for the Indonesian people who will perform the hajj, especially in minimizing fraud, convoluted bureaucracy, and non-transparent services. However, the hopes have not yet been fully realized in reality within the community. Therefore, this research aims to answer the extent to which the application of information technology in the management of hajj services can enhance public transparency and accountability, as well as identify the constraints and opportunities needed in the future to improve hajj services in Indonesia. This research uses case studies from various literature on related topics to see the extent of public satisfaction with IT-based hajj services. This study also uses a descriptive qualitative approach and literature analysis techniques. The research results show that information technology (IT) has a significant impact on public satisfaction as a positive appreciation of pilgrimage services. However, some of them also show weaknesses, such as the application services not being accessible to the entire community, the financial distribution reports being less transparent, and indications of fraud during the waiting period for hajj pilgrims. This then has implications for the public's expectations of services that should be easy and transparent and also serve as a form of integrity in fostering public trust in Hajj services, which is somewhat contrary to the reality in society